1977
DOI: 10.3758/bf03336944
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional social desirability inventory

Abstract: The hypothesis that the need for social approval may be viewed most adequately as a multidimensional construct consisting of at least partially independent dimensions was evaluated. An inventory was created and tested that measured independently each of four factors identified as operative in previous research in this area. Based on a conception of the importance of attribution and denial as central elements in self-descriptive statements differing in social desirability value, four scales were created measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 4 publications
1
27
0
2
Order By: Relevance
“…Forty students who participated in this study for course credit were randomly divided into two groups. The first group simply answered a few questions that asked for demographic information, the College Self-Expression Scale (CSES; Galassi, Delo, Galassi, & Bastien, 1974), a slight revision of the Learning Styles Questionnaire (LSQ; Schmeck, Ribich, & Ramanaiah, 1977), and the JacobsonKellogg social desirability scale (J-K; Jacobson, Kellogg, Maricauce, & Slavin, 1977). These instruments were chosen because of their inclusion in the major study reported in this paper.…”
Section: Bogus Pipeline Pilot Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Forty students who participated in this study for course credit were randomly divided into two groups. The first group simply answered a few questions that asked for demographic information, the College Self-Expression Scale (CSES; Galassi, Delo, Galassi, & Bastien, 1974), a slight revision of the Learning Styles Questionnaire (LSQ; Schmeck, Ribich, & Ramanaiah, 1977), and the JacobsonKellogg social desirability scale (J-K; Jacobson, Kellogg, Maricauce, & Slavin, 1977). These instruments were chosen because of their inclusion in the major study reported in this paper.…”
Section: Bogus Pipeline Pilot Studymentioning
confidence: 99%
“…The Jacobson-Kellogg Social Desirability Scale (J-K). The J-K scale (Jacobson, Kellogg, Maricauce, & Slavin, 1977) is a 68-item questionnaire that employs a true/false format and that measures need for approval. It was chosen because its more recent construction better reflects current social desirability values and because its greater length results in improved reliability over the Marlow-Crowne Scale.…”
Section: Subjects and Experimentersmentioning
confidence: 99%
“…Test-retest (intra-rater) reliability for the BIDR when using the continuous scoring procedure, as utilised in the present study, has been reported to be in the range of 0.70-0.82 for self-deception, and 0.80-0.86 for impression-management (Paulhus, 1994;Stober et al, 2002;Li and Bagger, 2006;Booth-Kewley et al, 1992). The BIDR shows concurrent validity, as a measure of self-deceptive responding, with the Marlowe-Crowne Social Desirability Scale (Crowne and Marlowe, 1960) and the Multidimensional Social Desirability Inventory (Jacobson et al, 1977). The EPI scale was included as the 'Lie' subscale probes whether subjects claim to regularly carry out rarely performed but socially-desirable acts, or deny indulging in frequently performed but non socially-desirable acts (Jackson and Francis, 1998).…”
Section: Hypothesesmentioning
confidence: 82%
“…Roth, Snyder i Pace, 1986). Jacobson, Kellogg, Cauce i Slavin (1977) pošli su od velike baze čestica kako bi razvili inventar socijalne poželjnosti koji eksplicitno razdvaja pripisivanje poželjnih osobina od negiranja nepoželjnih. Našli su da je interkorelacija podskala značaj-no niža od korelacija podskala s ukupnim rezultatom i prema tome zaključili da podskale mjere različite konstrukte.…”
Section: Pripisivanje Poželjnih Osobina Nasuprot Negiranju Negativnihunclassified